Obstetric outcomes and effects on babies born to women treated for epilepsy during pregnancy in a resource limited setting: a comparative cohort study - Priyadarshani Galappatthy; Chiranthi Kongala Liyanage; Marianne Nishani Lucas; Dilini T. L. M. Jayasekara; Sachith Aloka Abhayaratna; Chamari Weeraratne; Kusum De Abrew; Padma Sriyani Gunaratne; Ranjani Gamage; Chandrika N. Wijeyaratne (BMC, 2018)
Abstract Background Management of epilepsy during pregnancy in a resource-limited setting (RLS) is challenging. This study aimed to assess obstetric outcomes and effects on babies of women with epilepsy (WWE) exposed to Anti-epileptic drugs (AEDs) compared to non-exposed controls in a RLS. Methods Pregnant WWE were recruited from antenatal and neurology clinics of a tertiary care hospitals in Sri Lanka. Patients were reviewed in each trimester and post-partum. Medication adherence, adverse effects, seizure control and carbamazepine blood levels were monitored. Post-partum, measurements for anthropometric and dysmorphic features of the babies and congenital abnormalities were recorded. Age and sex matched babies not exposed to AED recruited as controls were also examined. Results Ninety-six pregnant WWE were recruited (mean period of gestation 22.9 weeks). Mean age was 28 years and 48(50%) were primigravidae. Fifty percent (48) were on monotherapy, while 23.8, 15.9 and 4.1% were on two, three and four AEDs respectively. AEDs in first trimester (TM1) were carbamazepine (71%), valproate (25.8%) clobazam (29.5%), lamotrigine (7%) topiramate (5%) and others (3.4%). Sodium valproate use reduced significantly from T1 to T2(p < 0.05). Sub-therapeutic carbamazepine levels correlated positively (r = 0.547) with poor medication adherence (p = 0.009) and negatively (r = 0.306) with adverse effects (p = 0.002). Seventy-six WWE completed follow-up reporting w 75 (98.6%) live births and one T1 miscarriage (1.3%). Three (4.3%) were preterm. Majority (73.33%) were normal vaginal deliveries. Cesarean sections were not increased in WWE. Fifty-nine (61.45%) babies were examined. For those examined during infancy, 53 age and sex matched controls were recruited and examined.. Congenital abnormalities occurred in 5 (9.43%) babies of WWE [atrio-ventricular septal defect (2), renal hypoplasia (1), cryptorchidism (1), microcephaly (1)] compared to 2 (3.77%) in controls (2 microcephaly; p = 0.24). Fetal exposure to AEDs increased a risk of low birth weight (RR 2.8; p = 0.049). Anthropometric parameters of AED exposed babies were lower at birth but not statistically significant between the two groups (weight p = 0.263, length p = 0.363, occipito-frontal circumference (OFC) p = 0.307). However, weight (p = 0.009), length (p = 0.016) and OFC (p = 0.002) were significantly lower compared to controls at an average of 3.52 months. Conclusion Most pregnancies are unplanned in the RLS studied, and AEDs were altered during pregnancy. Congenital anomalies occurred at rates comparable to previous reports. Fetal exposure to AED had growth retardation in infancy compared to non-exposed babies.